Dissipative Landau-Zener transitions in a three-level bow-tie model: accurate dynamics with the davydov multi-D2 ansatz - Zhang, Lixing (2024)
Landau-Zener (LZ) transitions in the three-level bow-tie model (3L-BTM) in a dissipative environment are investigated by using the numerically accurate method of multiple Davydov (Formula presented.) Ansätze. The 3L-BTM coupled to a single harmonic mode is first considered, and evolutions of transition probabilities for selected values of model parameters are studied and interpreted with the aid of the energy diagram method. Then the 3L-BTM coupled to a boson bath of a continuum spectral density is explored. The simulations demonstrate that sub-Ohmic, Ohmic and super-Ohmic boson baths have substantially different influences on the 3L-BTM dynamics, which cannot be grasped by the standard phenomenological Markovian single-rate descriptions. Novel bath-induced phenomena are also described, which are absent in two-level LZ systems.